Internet Access and Older Adults' Health: Evidence from China - Xiangyuan Ding; Luoqi Yuan; Yi Zhou (China Economic Review, 2023)
In the context of China's rapid population aging and internet expansion, this study examines the impact of information and communication technologies on the of older adults’ health. Using the China Health and Retirement Longitudinal Study 2011–2018, we find that internet access improves older adults' self-reported health, mental health, and activities of daily living (ADL). Further investigations provide evidence for several underlying mechanisms, including improving social participation, promoting healthy behaviors, and encouraging intergenerational interactions. Heterogeneity analyses show that disadvantaged groups, such as those with any ADL difficulty and without social participation or a spouse, benefit more from internet access.